Study of different germplasm of early summer maize in Rampur, Chitwan, Nepal - Adhikari, Indra Prasad; Osti, Bandana; Kunwar, C.B.; Ojha, B.R. (International Journal of Social Sciences and Management, 2021)
Fourteen different germplasms of early summer maize (Zea mays L.) were tested for their production potential. The main objective of this research was to see the productivity of these varieties on local condition, their phenotypic characters, and their relationship with yield. Fourteen trails with three replications were randomized with RCBD. Observation and data recording were done by field visiting. Among the observed quantitative parameters; Cob diameter, Cob length, Row number per cob, Grain number per row, 300 grain weight at 14% moisture shows positive and significant correlation with the yield whereas Days to 50% silking, Days to 50% tasseling, and plant height shows positive but non –significant correlation with the yield. COMPOZ-NI-PB, S03TEY-POBM, and EEYCL were seen more productive than the released variety of NMRP: Arun-4 on the local condition. Int. J. Soc. Sc. Manage. Vol. 8, Issue-2: 391-295